Pete Seeger Reader. - Cohen, Ronald D. (Oxford University Press, USA, 2013)
Perhaps the most widely recognized figure in folk music and one of the most well-known figures in American political activism, Pete Seeger now belongs among the icons of 20th-century American culture. The road to his current status as activist and respected voice of folk music was long and often rough, starting from the moment he dropped out of Harvard in the late 1930s and picked up a banjo. Editors Ronald Cohen and James Capaldi trace Seeger's long and storied career, focusing on his work as not only a singer, but also on his substantial contributions as an educator, songwriter, organizer, p.